Komparasi Sistem Pembuktian Hukum Acara Pidana Antara Indonesia Dengan Republik Rakyat Cina: Comparative Analysis of the Criminal Evidence Systems between Indonesia and the People's Republic of China - Muhammad Alvaro Syahputra; Dyah Setyorini (Faculty of Law, Universitas Trisakti, 2024)
Indonesia regulates its criminal proof system in the Indonesian Criminal Procedure Code, while China governs its proof system under the Criminal Procedure Law of the People's Republic of China. Although both Indonesia and China follow a Civil Law system, there are similarities and differences in their criminal proof systems. This study employs a normative legal research approach with a descriptive-analytical nature, utilizing secondary data analyzed qualitatively and drawing deductive conclusions. The research findings indicate that the similarity between the criminal proof systems of Indonesia and China lies in the presence of proof hearings during the trial process in both countries. The difference is found in the types of evidence admissible in court: Indonesia recognizes five types of evidence, whereas China acknowledges seven types.